Physical Education, Sport and Health as Intervention Stunting Prevention in Taraweang Village - Hezron Alhim Dos Santos; Sugirah Nour Rahman; Maria Herlinda Dos Santos; Benni Badaru; M. Awaluddin Amrin (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This study aims to determine the method of physical education as an intervention to prevent stunting in Taraweang village and the effect of physical education as an intervention to prevent stunting in Taraweang village. This study uses a class action research method. The object of this Action Research is Physical Education, Sports and Health. This research stage is through two cycles. The First Cycle consists of the Planning, Implementation (Action), Observation and Reflection stages which are then continued by the Second Cycle with the same stages. The conclusion in this study is that Physical Education as an Intervention for Stunting Prevention in Taraweang Village is carried out by incorporating stunting prevention material in the Physical Fitness Component Development Sub-material Related to Health and Skills by modifying the RPP and providing teaching media E-Book for Stunting Prevention in Adolescents. Physical education as an intervention to prevent stunting in Taraweang Village has shown a significant effect on increasing students' understanding of SMP 2 Labakkang regarding stunting prevention.